Determinan Risiko dan Pencegahan terhadap Kejadian Penyakit Diabetes Melitus Tipe 2 pada Usia Produktif di Wilayah DKI Jakarta: Determinants of Risk and Prevention of Type 2 Diabetes Mellitus in the Productive Age in the DKI Jakarta Area - Nina; Purnama, Hendy; Adzidzah, Herlingga Zahra Nurul; Solihat, Melisa; Septriani, Meti; Sulistiani (Journal of Public Health Education, 2023)
Background: Diabetes Mellitus is a collection of metabolic diseases characterized by high blood sugar levels (Hyperglycemia) resulting from abnormalities in insulin secretion, insulin function, or both. Type 2 Diabetes Mellitus often occurs in productive-age adolescents, where environmental factors such as a family history, obesity, unhealthy lifestyle, low consumption of fruits and vegetables, and ineffective physical activity contribute to its development. Objective: To assess the health status of the community based on the Risk Analysis and Prevention Behavior of Type 2 Diabetes Mellitus in Productive Age in the DKI Jakarta Area in 2021. Method: This research uses a quantitative descriptive method conducted online through the processing of primary data from Google Forms (Questionnaires) from March to August 2021 in the DKI Jakarta area. The respondents in this study are productive-age individuals (12-≥65 years old) totaling 599 respondents. Secondary data collection is done through the Health Profile of DKI Jakarta and several previous research journals. Results: The study indicates that Type 2 Diabetes Mellitus in Productive Age (12-25 years) is present in 441 individuals (73.6%), and the coverage of respondents at risk of Type 2 Diabetes Mellitus is 43 (7%), with a genetic disease risk percentage of 3.5% from 599 respondents. Other contributing factors include gender, with females at 1.8% and males at 1.2%, age groups 55-64 years (6.3%), 65-74 years (6.03%), and 45-54 years (3.9%). Conclusion: Type 2 Diabetes Mellitus in Productive Age is caused by three factors: genetics (family inheritance), behavior (regular physical activity, healthy food consumption, and smoking), and healthcare services (insufficient regular health check-ups).